Higher educational attainment among female than male students: the intervention to increase enrolment of male students in Malaysian tertiary institution - Ismail, L.; Darusalam, G. (2011)
The study aims to identify why academic performance differs between male and female students; to investigate why more females than males are at tertiary institution; and to assess current initiatives taken to increase male students’ enrolment in Malaysian tertiary institution. This quantitative and qualitative method of research utilizes data analysis from respondents from a matriculation centre of University Malaya students. The design of this study is cross-sectional and comparative in nature, and the instruments used are self-administered questionnaires and semi-structured interviews. The analysed data utilized frequency and percentage. The results revealed that male students’ level of maturity is slower than that of female students and thus it affects their academic performance; male students should be monitored, be motivated and given better educational opportunities in order to perform better in their studies. Female students have different characteristics that influence their educational attainment such as having better inspiration in their studies; females are more determined, dedicated, patient, ambitious and highly aspirated than males in achieving education. In light of these results, several suggestions were proposed for the solution and implication to increase the number of male students in tertiary institutions.